Islamic Religious Education Teacher Management In Developing Students' Al-Qur'an Reading Culture (Case Study Of SMA Negeri 10 and Sma Yas Bandung) - Diah Agustina Rachman; Sofyan Sauri; Helmawati (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
One of the characteristics of religious education is the activity of reading the Qur'an, the reality in PTQ's 2013 research showed that around 65% of Indonesians have not been able to read the Qur'an, steps are needed to develop a culture of reading the Qur'an. The purpose of this study was to obtain an overview of PAI teachers in developing students' Al-Quran reading culture. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that (1) Planning, with meeting activities, cultural programs for reading the Qur'an inside and outside the classroom, evaluation, facilities and infrastructure, availability of PAI teachers, and making BTQ schedules. (2) Implementation, by conducting Al-Qur'an guidance, exemplary, creating a conducive environment, communicating activities, encouraging parents and teachers to learn to read the Qur'an, habituation of students at school and outside of school, and student involvement in peer guidance (3) Evaluation, consisting of reading, writing, memorizing the Qur'an, and tajwid, (4) Supporting factors are PAI teacher commitment, student commitment, parental support, student support, students learning Al-Qur'an Qur'an to his parents and ustadz. The inhibiting factors are few PAI teachers, the level of student intelligence, limited time, parents are busy working, there is no decree to guide students and there is no incentive fund.